THE PERCEPTIONS OF THEATRE-BASED ACTIVITIES IN TESL AMONG TESL STUDENTS TO IMPROVE THEIR SPEAKING SKILLS IN ENGLISH - JEEVARATINAM, KAMALI; STEPHEN, VELVIENA STEPHENIE; GOBINATHAN, ANNICE MARIA (Selangor Humaniora Review, 2025)
Abstract This study investigates ESL students’ perceptions of theatre-based activities for enhancing English-speaking skills. It examines how participation in theatre affects students with confidence, fluency, and ability to overcome speaking problems. Many students struggle with speaking English because they have little experience with it and are anxious or afraid of making mistakes. Drama classes include activities such as improvisation, role play, and scripted performances provide students with an engaging and pressure-free environment to practice speaking. The study focuses on TESL students at the University of Selangor (UNISEL) who took Theatre in TESL as an elective subject in their B.Ed TESL programme. A total of 107 students participated in the survey and reported their experiences with theatre-based learning. The study adopted a quantitative approach using a structured questionnaire for data collection. Purposive sampling was used to ensure diversity and reliability of participant selection. The results show that students perceive role-playing and theatre activities as beneficial for building confidence and promoting spontaneous English communication. The study highlights the positive role of theatre in TESL and underlines its potential to improve speaking skills. Further research is recommended to investigate teaching strategies, learner attitudes, and the wider pedagogical impact of theatre-based learning. Keywords: TESL Students, Theatre-based Activities, English-speaking Skills, Self-confidence, Fluency, Speaking Challenges, Improvisation, Role-playing